The Deterioration of economic growth and lack of transparency in Bolivia: in view of the fall in gas exports, net international reserves, and the increase in foreign debt and fuel imports, Bolivia's economic growth has deteriorated - Vargas Díaz, César (2023)
The objective of this article is to offer a general vision of the deterioration of the economic growth of Bolivia, in the period 2013 to 2022, mainly of these macroeconomic variables of study such as the export of natural gas, net international reserves, external debt and imports of diesel and gasoline fuels, each of these variables are dependent on the foreign currency dollars. In this understanding, the deterioration is mainly due to the fall in gas exports, reserves and the increase in external debt and fuel imports, as reflected in historical data and where we have identified the four inflection stages. In the last stage, it was characterized by a shortage of dollars and a high demand for it by citizens and the government, added to the lack of transparency in the disclosure of information on net international reserves and dependence on non-renewable resources gives as result in deteriorating economic growth. In addition, Bolivia is characterized by not promoting science, knowledge, qualified human capital, research, development and technological innovation, which led to a high informal labor level and insufficient productive sustainability in foreign currency.